The Effect Of Tiktok Video On Knowledge And Behaviour Of Low Carbohydrate Diet Behaviour In Female College Students - Watu, Rislon K P; Maunita, Risda Dwi; Kolong, Sintia; Rayanti, Rosiana Eva (Poltekkes Kemenkes Banjarmasin, 2025)
Overweight among adolescents continues to rise globally, including in Indonesia, primarily due to unhealthy lifestyles and fast-food consumption. One weight-loss strategy is a low-carbohydrate diet, yet knowledge and behavior regarding this diet among young women remain limited. This study aimed to examine the effect of educational videos on TikTok on knowledge and behavior related to low-carbohydrate diets among female students. A quasi-experimental study with a one-group pre-test and post-test design was conducted. A total of 17 female students aged 18-25 years from Satya Wacana Christian University were selected using purposive sampling. Over one week, participants watched educational videos daily and were monitored through online sessions. There was an increase in knowledge (from 1 to 1.71) and dietary behavior (from 1.12 to 2.29) after the TikTok educational intervention. Before the intervention, 100% of participants had poor knowledge of the diet, which decreased to 76%, with 25% achieving good knowledge. Dietary behavior also improved, with the proportion of participants in the moderate category increasing from 23% to 35%, although low behavior still predominated. TikTok educational media effectively improved knowledge; however, additional support is needed to achieve significant behavioral changes. More intensive interventions and social support may help optimize outcomes.